Argentinatachoides, a new genus from Argentina putatively related to the Australian- Tasmanian Tasmanitachoides Erwin 1972 (Coleoptera: Carabidae: Bembidiini) - Sallenave, Ana Soledad (2008)
Argentinatachoides balli new genus, new species (Bembidiini) is described and illustrated and its microhabitat noted. Adults of this new species are found in Argentina, east of the Andean Cordillera, in Mendoza and La Rioja provinces. The sub-oblique notched anterior tibia and subulate apical palpomere are the attributes that place this genus within Subtribe Tachyina. Structural attributes, for example the elytral recurrent groove appearing double and the symmetrical basal lobes of the aedeagal median lobe indicate that this species is related to the Australian-Tasmanian genus, Tasmanitachoides Erwin. This discovery amplifies the known range of a particular fauna of Carabidae that was once widely distributed in the western part of Gondwana. Some aspects of the distribution of the group are discussed.